Association of genetic ancestry with HER2, GRB7 AND estrogen receptor expression among Colombian women with breast cancer - Rey-Vargas, Laura; Bejarano-Rivera, Lina María; Mejia-Henao, Juan Carlos; Sua, Luz F.; Bastidas-Andrade, Jhon Faustino; Ossa, Carlos Andrés; Gutiérrez-Castañeda, Luz Dary; Fejerman, Laura; Sanabria-Salas, María Carolina; Serrano-Gómez, Silvia J. (Frontiers in Oncology, 2022)
Background: Our previous study reported higher mRNA levels of the human epidermal growth factor receptor 2 (HER2)-amplicon genes ERBB2 and GRB7 in estrogen receptor (ER)-positive breast cancer patients with relatively high Indigenous American (IA) ancestry from Colombia. Even though the protein expression of HER2 and GRB7 is highly correlated, they may also express independently, an event that could change the patients’ prognosis. In this study, we aimed to explore the differences in ER, HER2 and GRB7 protein expression according to genetic ancestry, to further assess the clinical implications of this association. Methods: We estimated genetic ancestry from non-tumoral breast tissue DNA and assessed tumoral protein expression of ER, HER2, and GRB7 by immunohistochemistry in a cohort of Colombian patients from different health institutions. We used binomial and multinomial logistic regression models to test the association between genetic ancestry and protein expression. Kaplan-Meier and log-rank tests were used to evaluate the effect of HER2/GRB7 co-expression on patients’ survival. Results: Our results show that patients with higher IA ancestry have higher odds of having HER2+/GRB7- breast tumors, compared to the HER2-/GRB7- subtype, and this association seems to be stronger among ER-positive tumors (ER+/HER2+/GRB7-: OR=3.04, 95% CI, 1.47-6.37, p<0.05). However, in the multivariate model this association was attenuated (OR=1.80, 95% CI, 0.72-4.44, p=0.19). On the other hand, it was observed that having a higher European ancestry patients presented lower odds of ER+/HER2+/GRB7- breast tumors, this association remained significant in the multivariate model (OR=0.36, 95% CI, 0.13 - 0.93, p= 0.0395). The survival analysis according to HER2/GRB7 co-expression did not show statistically significant differences in the overall survival and recurrence-free survival. Conclusions: Our results suggest that Colombian patients with higher IA ancestry and a lower European fraction have higher odds of ER+/HER2+/GRB7- tumors compared to ER+/HER2-/GRB7- disease. However, this association does not seem to be associated with patients’ overall or recurrence-free survival.